Role of Pigeons in the Transmission of Avian Avulavirus (Newcastle Disease-Genotype VIId) to Chickens - Hany F. Ellakany; Ahmed R. Elbestawy; Hatem S. Abd El-Hamid; Rasha E. Zedan; Ahmed R. Gado; Ayman E. Taha; Mohamed A. Soliman; Mohamed E. Abd El-Hack; Ayman A. Swelum; Islam M. Saadeldin; Hani Ba-Awadh; Elsayed O.S. Hussein (Animals, 2019)
Newcastle disease is an acute fatal disease of poultry. The aim of this study was to determine the dynamics of the transmission of avian avulavirus (velogenic viscerotropic Newcastle disease-genotype VIId) from either intramuscularly (IM)- or intranasally (IN) infected 8-week-old Egyptian Baladi pigeons in contact with commercial Arbor Acres broiler chickens (4 weeks of age). The mortality of IM infected chickens and pigeons was 10/10 for chickens and 8/15 for pigeons, while the mortality of IN infected chickens and pigeons was 7/10 for chickens and only 1/15 for pigeons. The concentration of viral shedding in the oropharynx was higher than that in the cloaca for both IN and IM infected pigeons. Pigeons infected IN continued shedding the virus from the oropharynx from the 4th day post-infection (dpi) up to the 16th dpi, while IM infected pigeons stopped oropharyngeal shedding at the 11th dpi. Chickens in contact with infected pigeons developed severe respiratory, digestive and nervous signs. The mortality rates in chickens in contact with IM and IN infected pigeons were 2/5 and 3/5, respectively. Chickens in contact with IM infected pigeons showed higher viral shedding titres in both the oropharynx and cloaca than chickens in contact with pigeons infected IN. In conclusion, free-range pigeons are considered an efficient carrier and transmitter of NDV-VIId compared to commercial broiler chickens raised in open houses.